The Influence of Human Capital Adaptive Capacity Strategies on Organizational Performance Achievements Mediated by Adaptive E-Procurement Systems - Tatiek Ekawati Permana; Eeng Ahman; Tjutju Yuniarsih; Rofi Rofaida; Darul Wiyono (Khazanah Sosial, 2024)
Tourism is an important aspect of economic activity, especially in Indonesia which has superior natural resource potential. However, there is a gap between tourism potential and the quality of human resources in driving the tourism economy, resulting in low tourism competitiveness compared to other countries. This research aims to find the best formula for building a model for improving organizational performance and competitiveness in the hotel industry through a strategic human resource management approach. How much organizational performance is achieved depends on the performance of its people, regardless of the shape, size, goals and characteristics of the organization. In the context of research, some research results also still contain disagreements regarding the understanding of Human Capital Management, which is generally widely understood as performance measurement, as well as the Adaptive E-Procurement system. This research uses quantitative methods with partial least squares (PLS) analysis tools. In this case, the researchers took samples based on the total population of 19 five-star hotels and 94 4-star hotels, according to the Slovin formula, namely 88 samples. The results showed that HCACS-X2 had a significant positive effect on OPC-Y. The HCACS-X2 variable against OPC-Y has an original sample of 0.382 in a positive direction, meaning that the better the HCACS-X2, the OPC-Y will also increase by 0.382. HCACS-X2 has a significant positive effect on OPC-Y through AE-PS-X3. The HCACS-X2 variable against OPC-Y via EPSA has an original sample of 0.352 in a positive direction, meaning that the better the HCACS-X2 via AE-PS-X3, the OPC-Y will also increase by 0.352.